Caregiver burden and its prevalence, measurement scales, predictive factors and impact: a review with an Asian perspective - Yu Xian Loo; Shi Yan; Lian Leng Low (Singapore Medical Journal)
Caregiver burden is a well-recognised global phenomenon. The primary aim of this review is to summarise the prevalence of caregiver burden and its measurement scales, predictive factors and impact in Singapore. PubMed® and Scopus® databases were searched using the key terms ‘caregiver’, ‘burden’, ‘stress’, ‘strain’ and ‘Singapore’. A total of 206 papers were retrieved and 20 were included. This review showed that a significant proportion of caregivers in Singapore experience caregiver burden. Caregiving experiences and outcomes are affected by cultural, behavioural and socioeconomic factors. Being a Malay caregiver appears to be a protective factor for caregiver burden, whereas having negative coping strategies and care recipients with functional, cognitive and behavioural impairments are positive risk factors. As for outcomes, caregiver burden is associated with poorer self-rated health and reduced quality of life. Multiple instruments have been used to measure caregiver burden, and the Zarit Burden Interview is the most widely used.